Răspuns:
f(x)=2x-3
g(x)=f(x+3)=2(x+3)-3=
2x+6-3=2x+3
B)f(x)=2x-3
Intersectia cu Ox f(x)=0
2x-3=0
2x=3 x=3/2
A(3/2,0)
Intersecyia cuOy
f(0)=2*0-3=0-3= -3
B(0,-3)
Trasezi dreapta AB
g(x)=2x+3
Intersectia cu Ox
2x+3=0 2x= -3 x= -3/2 C(-3/2,0)
Intersectia cu Oy
g(0)=2*0+3=3
D(0,3)
Trasezi dreapta CD
c)f(-1)=2*(-1)-3= -2-3= -5
f(-2)=2*(-2)-3= -4-3= -7
------------------------------------
f(-25)=2(-25)-3= -50-3= -53
g(1)=2*1+3= 5
g(2)=2*2+3=7
----------------------
g(25)=2*25+3=53
g(26)=2*26+3=52+3=55
---------------------------------------------------------------------------------------
f(-1)+f(-2)+...+f(-25)+g(1)+g(2)+...+g(25)+g(26)=
-5-7-...-53+5+7+...+53+55= reduci termenii opusi=55
Asteapta atasamentul
Intersectia cu
Explicație pas cu pas: